Moc bezmocných: Some Thoughts from Afar. Issue 2 (May 2018) - Scruton, Roger
Havel's essay The Power of the Powerless described a unique situation in post-war Europe, when the Communist system of power was exhausted and those deprived of power under it were beginning to know each other and cooperate with each other in a new kind of underground. I describe the spiritual condition of a certain kind of young person in this underground, eager to find another cultural identity than the one offered by the official ideology and anxious to "live in truth." I suggest that the sudden collapse of Communism and the advent of a new consumer society left those young people in a certain measure bereft.